5 - Philosophie et politique: Pour une discussion avec Lansana Keita: 10.4314/ad.v29i1.22187 - Hountondji , Paulin (Africa Development, 2004)
In an exchange of ideas with the guest editor, Paulin Hountondji discusses ten ( 10) theoretical questions on the historical role of critical thought in establishing the parameters for the economic, political, and technological transformation of African society. The set of questions put to Hountondji deal with the historical role played by philosophers in the qualitative transformation of society of the economic systems of socialism and capitalism as they apply to Af economic and technological underdevelopment of contemporary Af relation between science, philosophy and development, the ideas of theo as Nkrumah, Fanon and Diop, and the role of an African history of ide formulating of a programme of development. In this exchange Hountondji issues about how to transform critical philosophical theory into a dynam of economics, politics, science and technology. Hountondji's discussio modo, emphasizes the necessity for independent critical thought, a reco the importance of an African history of ideas, and the necessity fo intellectuals to develop autonomous intellectual centres. Hountondji a for a 'philosophie engagée' that develops in the right direction but nece consort with the ideas of other critical intellectual efforts and programm regard, the critique of ethnophilosophy has cleared the way for a ho dynamic programme for African development in all its dimensions.